2003
DOI: 10.14411/fp.2003.024
|View full text |Cite
|
Sign up to set email alerts
|

Life cycle of the temporary fish parasite, Gnathia africana (Crustacea: Isopoda: Gnathiidae)

Abstract: Abstract. Laboratory work was conducted to elucidate the life cycle of the South African gnathiid isopod, Gnathia africana Barnard, 1914. The natural fish hosts of this temporary parasite, the super klipfish Clinus superciliosus (Linnaeus, 1758), were exposed to gnathiid larvae in the laboratory. It was found that G. africana has three larval stages, consisting of three unfed (zuphea) and three fed (praniza) stages. First-, second-and third-stage zuphea larvae took an average of 2 h 18 min, 2 h 43 min and 10 h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
72
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(74 citation statements)
references
References 14 publications
2
72
0
Order By: Relevance
“…obtained in our samples were males. The lower abundance of females in sponges was also reported by Smit et al (2003) and Barnard (1914); the latter author found the females inhabiting the tubes of serpulid worms. Three other species of isopods were found in the studied sponge, Fissarcturus patagonicus (Ohlin, 1901), Acanthoserolis schythei (Lütken, 1858) and Iathrippa sp., but each species was represented by one or two individuals.…”
Section: Discussionsupporting
confidence: 66%
“…obtained in our samples were males. The lower abundance of females in sponges was also reported by Smit et al (2003) and Barnard (1914); the latter author found the females inhabiting the tubes of serpulid worms. Three other species of isopods were found in the studied sponge, Fissarcturus patagonicus (Ohlin, 1901), Acanthoserolis schythei (Lütken, 1858) and Iathrippa sp., but each species was represented by one or two individuals.…”
Section: Discussionsupporting
confidence: 66%
“…2). They become swollen with fish blood when feeding, normally drop off when replete and digest the blood meal, moult and then re-attach to fishes, feeding three times in this manner (see Smit et al 2003b). Gnathiid larvae are therefore capable of drawing blood with H. bigemina from infected fishes and on at least three occasions during their development.…”
Section: Transmissionmentioning
confidence: 99%
“…Biological transmission to clean fishes under laboratory conditions should be, therefore, another logical aim for the future. The apparent broad distribution of H. bigemina among fishes, the ease with which gnathiids can be persuaded to feed on these hosts (see Smit et al 2003b) and the fact that many fishes eat gnathiids, may all aid attempts at transmission. Another important question is, does H. bigemina truly have an intraleukocytic phase or are mixed infections involved?…”
Section: Future Researchmentioning
confidence: 99%
“…The amount of time required for gnathiids to become fully engorged varies among both species and developmental stages, with feeding period being longer for larger species and later juvenile stages (Grutter 2003;Smit et al 2003;Smit and Davies 2004). Gnathiids can become engorged in less than 10 minutes (Grutter 2003) but can attach for up to 10 h (Grutter 2003;Smit et al 2003;Grutter et al 2011).…”
Section: Ecological Importance Of Parasitesmentioning
confidence: 99%
“…'permanent' parasites such as copepods (Finley and Forrester 2003) and cymothoid isopods (Adlard and Lester 1994;Roche et al 2013a), and those that remain on the host only briefly while feeding, i.e. 'temporary' parasites such as gnathiid (Smit et al 2003;Ota et al 2012) and corallanid isopods (Grutter and Lester 2002), which are often classified as mobile micropredators (Lafferty and Kuris 2002). Surprisingly, only a few studies have tested the effect of L. dimidiatus on parasite loads.…”
Section: Chapter 5: Diel Patterns Of Infection By Gnathiid Isopods Onmentioning
confidence: 99%